To keep or not to keep? Decision making in adolescent pregnancies in Jamestown, Ghana - Amoakoh-Coleman, M.; Bain, L.E.; Zweekhorst, M.B.M.; Muftugil-Yalcin, S.; Omolade, A.I.O.; Becquet, R.; Buning, T.D.C. (Plos One, 2019)
Background Jamestown, an urban coastal slum in Accra, Ghana, has one of the highest adolescent pregnancy rates in the country. We sought to understand the decision (to keep or terminate) factors and experiences surrounding adolescent pregnancies. Methods Thirty semi-structured indepth interviews were carried out among adolescents (aged 13–19 years) who had been pregnant at least once. Half of these were adolescent mothers and the other half had at least one past experience of induced abortion. A pretested and validated questionnaire to assess the awareness and use of contraception in adolescent participants was also administered. To aid social contextualization, semi-structured in depth interviews were carried out among 23 purposively selected stakeholders. Results The main role players in decision making included family, friends, school teachers and the partner, with pregnant adolescents playing the most prominent role. Adolescents showed a high degree of certainty in deciding to either abort or carry pregnancies to term. Interestingly, religious considerations were rarely taken into account. Although almost all adolescents (96.1%) were aware of contraception, none was using any prior to getting pregnant. Of the 15 adolescents who had had abortion experiences, 13 (87.0%) were carried out under unsafe circumstances. The main barriers to accessing safe abortion services included poor awareness of the fairly liberal nature of the Ghanaian abortion law, stigma, high cost and non-harmonization of safe abortion service fees, negative abortion experiences (death and bleeding), and distrust in the health care providers. Adolescents who chose to continue their pregnancies to term were motivated by personal and sociocultural factors.Conclusion Decision-making in adolescent pregnancies is influenced by multiple external factors, many of which are modifiable. Despite legal access to services, options for the safe termination of pregnancy or its prevention are not predominantly taken, resulting in a high number of negative experiences and outcomes. Including safe abortion care within the sexual and reproductive health package, could diminish barriers to safe abortion services. Given the vulnerability of the Jamestown setting, a comprehensive sexual education package that addresses the main decision factors is recommended. Interventions aiming to reduce adolescent pregnancy rates should also recognize that adolescent pregnancies are culturally acceptable in some settings, and under certain circumstances, are desired by the adolescents themselves.
Research Article
Keywords: Jamestown; coastal slum; Ghana; pregnancy rates